Stable neuropsychiatric status in multiple sclerosis: a 3-year study. (April 2016) - Roy, Shumita; Rodgers, Jonathan; Drake, Allison S; Zivadinov, Robert; Weinstock-Guttman, Bianca; Benedict, Ralph HB
Personality changes and neuropsychiatric symptoms are found in multiple sclerosis (MS), but no study has evaluated decline compared to healthy controls. This study assessed personality traits and neuropsychiatric symptoms over 3 years using the NEO Five Factor Inventory and the Neuropsychiatric Inventory. Additional metrics evaluated ambulation, manual dexterity and cognitive function. Contrary to hypothesis, patients showed no significant change in personality or neuropsychiatric status relative to controls. Patients were impaired in motor and cognitive function at baseline and follow-up, but showed only slowing in ambulation over time. The findings indicate that neuropsychiatric status is stable in MS over 3 years.